الأضرار الناجمة عن التلوث البيئي والقانون الواجب التطبيق عليها - الاتروشي, محمد جلال حسن (Journal of Legal and Political Studies, 2013)
Has taken over some legislation, including the Iraqi legislation in order to organize preservation of the environment from pollution, and that under the Law to Protect and Improve the Environment No. 27 1999, also the Environmental Law of Kurdistan Regional No.3 2010. Because of the increasing damage to the environment and the expansion its risks and sources, which requires us a statement of the applicable law and the Iraqi legislature has stipulated it in the Article (27) of the Iraqi Civil Law, taking into account the basic principles in Private International Law.
Keywords: Environment; Pollution; applicapable law; Private International Law